Modern humanity: global threats and the future - Rakhmanov, Sergei K. (Journal of the Belarusian State University. Sociology, 2026)
The article examines the process of transformation of humanity under the influence of new challenges and risks. It notes that all aspects of global society and the global ecosystem, including the environment and human consciousness, are facing increasing threats. Of particular concern is the lack of genuine global governance focused on ensuring the global interests of humanity, despite the presence of various international organisations that claim to represent global interests. Instead, private interests prevail, often contradicting global interests, with constant attempts to disguise these private interests as global ones. There is no global development strategy with a vision of an adequate future and ways to achieve it. It is indicated that as humanity transforms as a biosocial system, the role of its social component increases. However, until now, it is the humanistic mechanisms of social transformation that remain on the periphery of human attention.